PACAP–PAC1 Signaling Regulates Serotonin 2A Receptor Internalization - Hayata-Takano, Atsuko; Shintani, Yusuke; Moriguchi, Keita; Encho, Naoki; Kitagawa, Kohei; Nakazawa, Takanobu; Hashimoto, Hitoshi (Frontiers in Endocrinology, 2021)
Mice lacking pituitary adenylate cyclase-activating polypeptide (PACAP) display psychomotor abnormalities, most of which are ameliorated by atypical antipsychotics with serotonin (5-HT) 2A receptor (5-HT2A) antagonism. Heterozygous Pacap mutant mice show a significantly higher hallucinogenic response than wild-type mice to a 5-HT2A agonist. Endogenous PACAP may, therefore, affect 5-HT2A signaling; however, the underlying neurobiological mechanism for this remains unclear. Here, we examined whether PACAP modulates 5-HT2A signaling by addressing cellular protein localization. PACAP induced an increase in internalization of 5-HT2A but not 5-HT1A, 5-HT2C, dopamine D2 receptors or metabotropic glutamate receptor 2 in HEK293T cells. This PACAP action was inhibited by protein kinase C inhibitors, β-arrestin2 silencing, the PACAP receptor PAC1 antagonist PACAP6-38, and PAC1 silencing. In addition, the levels of endogenous 5-HT2A were decreased on the cell surface of primary cultured cortical neurons after PACAP stimulation and were increased in frontal cortex cell membranes of Pacap−/− mice. Finally, intracerebroventricular PACAP administration suppressed 5-HT2A agonist-induced head twitch responses in mice. These results indicate that PACAP–PAC1 signaling selectively increases 5-HT2A internalization resulting in attenuation of 5-HT2A-mediated signaling and thus offer a potential target for drug development.